Decomplexation Performance of Cu–EDTA and Parameter Optimization by Three-Dimensional Electro-Fenton - Ma, Yameng; Huang, Xiao; Han, Qi; Yu, Jianghua; Yu, Fengjiao; Zhu, Jia (Frontiers in Environmental Science, 2022)
The strong stability and low biodegradability of Cu-ethylenediaminetetraacetic acid (Cu-EDTA) result to the low decomplexation efficiency by traditional Fenton process. For breaking this limitation, a three-dimensional electro-Fenton (3D-EF) system was developed to study the Cu-EDTA removal at different pH values, and the effects of Fe2+ concentration, particle electrode dosage, current density and coexisting ions on Cu-EDTA removal were investigated. The results showed that the 3D-EF reaction system exhibited higher pollutant removal efficiency in a wide pH range compared with the traditional electro-Fenton (EF) process. 90.95% Cu-EDTA was removed after 120 min at pH=7, 1 mmol L-1 Fe2+, 2 g L-1 granular activated carbon and current density of 10 mA cm-2. In addition, the presence of Cl- slightly improved the decomplexation efficiency, whereas the presence of NO3- and HPO42- inhibits the removal of Cu-EDTA. The kinetics of the removal efficiency of Cu-EDTA in all experimental groups followed the first-order kinetic.